ANESTHESIA FOR CAESAREAN SECTION IN A PATIENT WITH PULMONARY HYPERTENSION AFTER CORRECTED COMPLEX HEART DEFECT - Karadjova, Dafina; Sivevski, Atanas; Mehmedovikj, Nadica; Kjaev, Ivo; Naumovska, Rosa; Kochoski, Goran (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Advances in medicine, especially in the treatment of congenital heart disease, are making it possible for many women with severe congenital heart disease to reach childbearing age and, of course, if they want to become pregnant and become mothers. 3-10% of those registered with congenital heart disease will develop pulmonary hypertension, which is always a poor prognostic sign and has particularly high mortality and morbidity, especially when undergoing operative treatment and anesthesia. We present a case of successful anesthetic management for the caesarean section in a patient with pulmonary hypertension after a complex congenital heart defect corrected in childhood. The anesthesiology approach is always challenging and requires an individual and multidisciplinary approach to each individual patient.
Keywords: anesthetic approach; caesarean section; pulmonary hypertension